Olaparib and advanced ovarian cancer: Summary of the past and looking into the future - Maiorano, Brigida Anna; Maiorano, Mauro Francesco Pio; Maiello, Evaristo (Frontiers in Pharmacology, 2023)
Ovarian cancer (OC) is women's eighth most common cancer, bearing the highest mortality rates of all female reproductive system malignancies. Poly (ADP-ribose) polymerase inhibitors (PARPis) have reshaped the treatment scenario of metastatic OC as a maintenance post platinum-based chemotherapy. Olaparib is the first PARPi developed for this disease. Results from Study 42, Study 19, SOLO2, OPINION, SOLO1, and PAOLA-1 clinical trials, led to the FDA and EMA approval of olaparib for the maintenance treatment of women with high-grade epithelial ovarian, fallopian tube, or primary peritoneal cancer without platinum progression: in the platinum-sensitive recurrent OC; in the newly diagnosed setting in case Breast Cancer (BRCA) mutations and, in combination with bevacizumab, in case of BRCA mutation or deficiency of homologous recombination genes. In this review, we synthetized olaparib's pharmacokinetic and pharmacodynamic properties and its use in special populations. We summarized the efficacy and safety of the studies leading to the current approvals and discussed the future developments of this agent.